2021
DOI: 10.3389/fphar.2021.671563
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Riboside Enhances Endothelial Precursor Cell Function to Promote Refractory Wound Healing Through Mediating the Sirt1/AMPK Pathway

Abstract: Lack of vascularization is directly associated with refractory wound healing in diabetes mellitus (DM). Enrichment of endothelial precursor cells (EPCs) is a promising but challenging approach for the treatment of diabetic wounds. Herein, we investigate the action of nicotinamide riboside (NR) on EPC function for improved healing of diabetic wounds. Db/db mice that were treated with NR-supplemented food (400 mg/kg/d) for 12 weeks exhibited higher wound healing rates and angiogenesis than untreated db/db mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 68%
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in place within the gel, avoiding the risk of exudate leakage as well as macerating the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…41 There is plenty of evidence supporting the metabolic benefits of NR provided by SIRT1. 40,42 In addition, the activation of SIRT1 can alleviate a multitude of NF-κB-driven inflammation, which have been confirmed by a series of in vitro and in vivo studies. 43 SIRT1 is able to bind to the RelA/p65 subunit of NF-κB and deacetylate RelA/p65 at lysine 310, a key site for NF-κB transcriptional activity.…”
Section: Discussionmentioning
confidence: 78%
“…Meanwhile, it significantly inhibited the expression of hypoxia-inducible factor 1-Alpha (HIF-1α) as well as its downstream TPI1 (Figure 5G). 23,24 These results partially explained the declined glycolysis levels in those AIA monocytes overexpressing SIRT1. Besides, phosphorylation of STAT3 (a transcriptional factor controlling M2 polarization) was inhibited in AIA monocytes compared to normal control, which was restored by SIRT1 overexpression (Figure 5G).…”
mentioning
confidence: 80%